Digital health solution for monitoring and surveillance of Amyotrophic Lateral Sclerosis in Brazil - Barbalho, Ingridy M. P.; Fonseca, Aleika L. A.; Fernandes, Felipe; Henriques, Jorge; Gil, Paulo; Nagem, Danilo; Lindquist, Raquel; Lima, Thaisa; Santos, João Paulo Queiroz dos; Paiva, Jailton; Morais, Antonio H. F.; Dourado Júnior, Mário E. T.; et al. (Frontiers in Public Health, 2023)
Amyotrophic Lateral Sclerosis (ALS) is a complex and rare neurodegenerative disease given its heterogeneity. Despite being known for many years, few countries have accurate information about the characteristics of people diagnosed with ALS, such as data regarding diagnosis and clinical features of the disease. In Brazil, the lack of information about ALS limits data for the research progress and public policy development that benefits people affected by this health condition. In this context, this article aims to show a digital health solution development and application for research, intervention, and strengthening of the response to ALS in the Brazilian Health System. The proposed solution is composed of two platforms: the Brazilian National ALS Registry, responsible for the data collection in a structured way from ALS patients all over Brazil; and the Brazilian National ALS Observatory, responsible for processing the data collected in the National Registry and for providing a monitoring room with indicators on people diagnosed with ALS in Brazil. The development of this solution was supported by the Brazilian Ministry of Health (MoH) and was carried out by a multidisciplinary team with expertise in ALS. This solution represents a tool with great potential for strengthening public policies and stands out for being the only public database on the disease, besides containing innovations that allow data collection by health professionals and/or patients. By using both platforms, it is believed that it will be possible 1 Barbalho et al.to understand the demographic and epidemiological data of ALS in Brazil, since the data will be able to be analyzed by care teams and also by public health managers, both in the individual and collective monitoring of people living with ALS in Brazil.